Role of TP53 Mutations and EGFR Amplification in Risk Stratification of Early‐Stage EGFR‐Mutated Non‐Small Cell Lung Cancer With Immunohistochemistry as a Surrogate Marker - Meejeong Kim; Gyeong Sin Park; Kyo Young Lee; Seok Whan Moon; Yeoun Eun Sung (Thoracic Cancer)
ABSTRACT Background Non‐small cell lung carcinoma (NSCLC) is a leading cause of cancer‐related mortality, with recurrence risks posing significant challenges in early‐stage disease management. While epidermal growth factor receptor (EGFR) mutations are common, the role of concurrent genetic alterations remains underexplored, and findings have often been inconsistent, particularly in early‐stage tumors. Methods We retrospectively analyzed 424 EGFR‐mutated NSCLC patients diagnosed from 2017 to 2022. Next‐generation sequencing (NGS) was used to identify genetic alterations, and immunohistochemistry (IHC) was employed to correlate TP53 mutations and EGFR amplification with protein expression. Survival outcomes were assessed using Kaplan–Meier and Cox regression analyses, while predictive cutoffs were determined with receiver operating characteristic (ROC) curve analysis. Results TP53 mutations and EGFR amplification were more prevalent in Stages 2–4 compared to Stage 1 (p < 0.001 and 0.005, respectively). In Stage 1, TP53 mutations, particularly exon 4 and frameshift/nonsense types, were associated with worse overall survival (OS) and disease‐free survival (DFS). EGFR amplification was linked to shorter DFS in Stage 1 (p = 0.006). Both alterations correlated with aggressive pathological features, including advanced N stage, lymphovascular invasion, and high histological grade. IHC cutoffs of 15% for TP53 and H‐score ≥ 180 for EGFR amplification demonstrated high predictive accuracy (AUC = 0.981 and 0.936, respectively). Conclusion Specific subtypes of TP53 mutations and EGFR amplification are important prognostic markers in early‐stage NSCLC. IHC offers a practical surrogate for genetic testing, aiding in risk stratification and guiding adjuvant therapy decisions for high‐risk patients. Larger validation studies are warranted.